Assessment of vegetation water content in wheat using near and shortwave infrared SPOT-5 Data in an irrigated area - Benabdelouahab, Tarik; Balaghi, Riad; Hadria, Rachid; Lionboui, Hayat; Tychon, Bernard (Revue des sciences de l’eau / Journal of Water Science, 2016)
In Morocco, water availability is becoming a national priority for the agricultural sector. In this context, the stakeholders try continuously to improve strategies of water irrigation management, on one hand, and to assess vegetation water content status, on the other hand, in order to improve irrigation scheduling and prevent water stress that affects yield adversely. The aim of this study was to evaluate the potential of two spectral indices, calculated from SPOT-5 high resolution visible (HRV) data, to retrieve the vegetation water content values of wheat in an irrigated area. These indices were the normalized difference water index (NDWI) and the moisture stress index (MSI). The values of these indices were compared with corresponding values of in situ-measured vegetation water content in 16 fields of wheat during the 2012-2013 cropping season. Good correlations were found between observed vegetation water content values and NDWI and MSI values during the crop growth period from anthesis to grain filling. These results were validated using the k-fold cross validation method and showed a good stability of the proposed regression models with a slight advantage for the NDWI. Based on these results, the NDWI was chosen to map the spatial variability of vegetation water content of wheat at the east of the Beni-Moussa irrigated perimeter. These results proved that the indices based on near and shortwave infrared band (NIR and SWIR) are able to monitor vegetation water content changes in wheat from anthesis to the grain filling stage. These indices could be used to improve irrigation and crop management of wheat at both the field and regional levels.